Evaluation of Mungbean (Vigna Radiata (L.) Wilczek) Genotypes on the Basis of Photosynthesis and Dry Matter Accumulation - Hossain, MA; Hamid, A; Khaliq, MA (Journal of Agriculture & Rural Development, 2010)
The study was carried out to evaluate six mungbean genotypes on the basis of photosynthesis and productivity under two levels of nitrogen. GK3 was found to have highest photosynthesis rate as well as the highest productivity among the six genotypes followed by VC6144A, PDM54 and IPSA25 irrespective of N levels. Key words: Mungbean, genotypes, photosynthesis. DOI: 10.3329/jard.v7i1.4415 J Agric Rural Dev 7(1&2), 1-8, June 2009